Regulatory sandboxing in Indonesia's fintech industry - Trissia Wijaya (Center for Indonesian Policy Studies (CIPS), 2023)
To accommodate Indonesia's quickly growing fintech industry, regulators have opted for a regulatory sandbox mechanism that bases the country's regulatory response to innovation on the results of live experiments. While they offer clear benefits, regulatory sandboxes can also be risky regulatory instruments. This paper assesses the promises and pitfalls of the sandbox, focusing on the digital financial innovation (DFI) sector, a responsibility of Indonesian Financial Services Authority (Otoritas Jasa Keuangan, or OJK). The paper focuses on sandbox governance, its risk management mechanism, and co-regulation.
Keywords: 330; Finanztechnologie; Regulierung; Risikomanagement; Indonesien